Computationally efficient and secure anonymous authentication scheme for IoT‐based mobile pay‐TV systems. (21st February 2020) - Kumaravelu, Ramesh; Sadaiyandi, Rajakumar; Selvaraj, Anandamurugan; Selvaraj, Jeeva; Karthick, Gayathiri
Abstract: In the next few years, the mobile pay‐TV systems will be very popular due to their extensive applications. Providing security and privacy are the most challenging issues in the secure development of mobile pay‐TV systems. To avoid unauthorized access to mobile pay‐TV services, it is very important to authenticate the mobile users and the head end system (HES) in an anonymous manner. Even though several authentication schemes were proposed to provide anonymous authentication, the previously proposed schemes are not fit for mobile pay‐TV applications due to their high computational complexity. Hence, a computationally efficient anonymous authentication scheme is proposed in this article for secure service provision in mobile pay‐TV systems. The proposed authentication scheme can effectively authenticate both the mobile users and the HES with low computational cost in an anonymous manner. In addition, an anonymous batch authentication scheme is also proposed in this article to authenticate a batch of users in the subscription phase to alleviate the authentication burden of the HES. The security analysis section shows that the proposed scheme is more efficient in terms of security and the performance analysis section shows the strength of this article in terms of computational cost, while performing anonymous authentication in mobile pay‐TV systems.